Effect of garlic oil on lamb fattening performance, rumen fermentation and blood parameters - Canbolat, Onder; Kamalak, Adem; Kalkan, Hatice; Kara, Huseyin; Filya, Ismail (Progress in Nutrition, 2021)
The objective of this study was to determine the effects of garlic essential oil (GEO) on performance, ruminal fermentation and blood parameters of Kivircik lambs. Forty-eight 2.5-3 month old Kivircik male lambs were allocated into four treatment groups. Diets were supplemented with GEO at the 0.0, 0.4, 0.8 and 1.2 g/kg DM. The growth trial lasted for 63 days. The supplementation of GEO significantly decreased the total weight gain (TWG) and average daily weight gain (ADWG), whereas it has no effect on the final body weight (FBW) daily feed intake (DFI) and feed conversion ratio (FCR). The supplementation of GEO to the lamb diets had also a significant impact on rumen fermentation and blood parameters. The addition of GEO to the lamb diets increased non-esterified fatty acid production while supplementation significantly reduced the levels of glucose, urea, protein, triglyceride, insulin and cholesterol. It can be said that the decrease of glucose, urea, triglyceride, insulin and cholesterol is important in terms of animal health when the blood parameters are taken into consideration. As conclusion, GEO supplementation up to 0.8 g/kg DM can be recommended for growing lambs to manipulate rumen and blood parameters without compromising important growth parameters.